Capacitor, dielectric for capacitor, electric circuit, circuit board, and device

JP7630084B2Active Publication Date: 2025-02-17PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024571410
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-03-03
Filing Date
2024-02-21
Publication Date
2025-02-17
Estimated Expiration
2044-02-21

AI Technical Summary

Benefits of technology

【0012】 本開示によれば、複合酸化物を含む誘電体を用いつつ、静電容量及び絶縁破壊電界の観点から有利なキャパシタを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630084000002
    Figure 0007630084000002
  • Figure 0007630084000003
    Figure 0007630084000003
  • Figure 0007630084000004
    Figure 0007630084000004
Patent Text Reader

Abstract

The present disclosure provides a capacitor advantageous in terms of capacitance and a dielectric breakdown field. A capacitor (1a) according to the present disclosure comprises: a first electrode (11); a second electrode (12); and a dielectric (20). The dielectric (20) is disposed between the first electrode (11) and the second electrode (12). The dielectric (20) contains a composite oxide. The composite oxide is composed of W and at least one selected from the group consisting of Cs, Ti, Zr, and Hf.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to capacitors, dielectrics for capacitors, electric circuits, circuit boards, and devices. [Background technology]

[0002] Dielectrics containing composite oxides are known.

[0003] For example, Patent Document 1 describes an integrated circuit including a non-ferroelectric high-k insulator. The insulator includes a thin film of a metal oxide. As the metal oxide, a pyrochlore-type oxide having the general formula A2B2O7 is described. A represents an A-site atom selected from the group of metals consisting of Ba, Bi, Sr, Pb, Ca, K, Na, and La. B represents a B-site atom selected from the group of metals consisting of Ti, Zr, Ta, Hf, Mo, W, and Nb.

[0004] Non-Patent Document 1 describes the dielectric properties of Nd2Hf2O7, a pyrochlore type crystal.

[0005] Non-Patent Document 2 describes the improvement of BaTa2O6 thin films for application to gate insulators in thin film transistors (TFTs). This document describes the variation of the dielectric constant of BaTa2O6 thin films with respect to oxygen partial pressure.

[0006] Non-Patent Document 3 describes the measurement results of the dielectric constant of a BaNb2O6 thin film. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 2003-502837 [Non-patent literature]

[0008] [Non-Patent Document 1] J. Chun et al. “Promising high-k dielectric permittivity of pyrochlore-type crystals of Nd2Hf2O7”, Journal of Materials Chemistry C, 2015, 3, 491-494 [DOI:https: / / doi.org / 10.1039 / C4TC02416H] [Non-Patent Document 2] Son Bui Tien et al. “Improvement of BaTa2O6 Thin Films for TFT Gate Insulator Applications”, The 66th JSAP Spring Meeting, 2019, [URL:https: / / www.researchgate.net / publication / 332216973_Improvement_of_BaTa2O6_Thin_Films_for_TFT_Gate_Insulator_Applications] [Non-Patent Document 3] DW KIM et al. “Cryatallographic orientation dependence of the dielectric constant in polymorphic BaNb2O6 thin films deposited laser ablation”, Phys. A 79, 677-680 (2004) [DOI:10.1007 / s00339-003-2232-3] Summary of the Invention [Problem to be solved by the invention]

[0009] The technology described in the above document has room for reexamination from the viewpoints of the capacitance and dielectric breakdown field of a capacitor while using a dielectric material containing a complex oxide.

[0010] Therefore, the present disclosure provides a capacitor that uses a dielectric material containing a complex oxide and is advantageous in terms of capacitance and dielectric breakdown field. [Means for solving the problem]

[0011] The capacitor of the present disclosure comprises: A first electrode; A second electrode; a dielectric material including a complex oxide and disposed between the first electrode and the second electrode; The composite oxide is Cs and At least one selected from the group consisting of Ti, Zr, and Hf; W and Effect of the Invention

[0012] According to the present disclosure, it is possible to provide a capacitor that is advantageous in terms of capacitance and dielectric breakdown field while using a dielectric material containing a complex oxide. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a capacitor according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of a capacitor according to the present disclosure. [Diagram 3] FIG. 3 is a cross-sectional view showing yet another example of a capacitor according to the present disclosure. [Figure 4] FIG. 4 is a cross-sectional view showing yet another example of a capacitor according to the present disclosure. [Diagram 5] FIG. 5 is a diagram illustrating a schematic example of an electric circuit according to the present disclosure. [Figure 6] FIG. 6 is a diagram illustrating an example of a circuit board according to the present disclosure. [Figure 7] FIG. 7 is a schematic diagram illustrating an example of the device of the present disclosure. [Figure 8] FIG. 8 is a diagram showing a schematic diagram of an evaluation method for the relative dielectric constant of the dielectric material according to each example. [Figure 9] FIG. 9 is a graph showing X-ray diffraction (XRD) patterns of the dielectric materials according to Examples 1, 2, and 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] (Findings on which this disclosure is based) Conventionally, in a capacitor having a dielectric material containing a complex oxide, a combination of elements contained in the complex oxide has been studied. For example, according to Patent Document 1, the A-site atom in a pyrochlore oxide having the general formula A2B2O7 is selected from the group of metals consisting of Ba, Bi, Sr, Pb, Ca, K, Na, and La. In addition, the B-site atom in the pyrochlore oxide is selected from the group of metals consisting of Ti, Zr, Ta, Hf, Mo, W, and Nb. Patent Document 1 lists the following pyrochlore oxides: (Ba x Sr 1-x )2(Ta y Nb 1-y )2O7, which satisfies the conditions 0≦x≦1.0 and 0≦y≦1.0. The metal oxide material described in Patent Document 1 has a relatively high dielectric constant and is used in integrated circuits.

[0015] On the other hand, in terms of the characteristics of a capacitor, it is important that the dielectric constant of the dielectric is high from the viewpoint of the capacitance of the capacitor, and the dielectric breakdown field, which is the upper limit of the electric field that can be applied to the dielectric, is also important.

[0016] Therefore, the present inventors have conducted extensive research to develop a capacitor that is advantageous in terms of high capacitance and high dielectric breakdown field. As a result, they have newly discovered that by using a dielectric material containing a complex oxide made of a combination of elements not described in the above documents, the capacitance of the capacitor is likely to be high and the dielectric breakdown field is likely to be high. Based on this new knowledge, the present inventors have devised the capacitor according to the present disclosure.

[0017] (Embodiments of the present disclosure) Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0018] FIG. 1 is a cross-sectional view showing an example of a capacitor of the present disclosure. As shown in FIG. 1, the capacitor 1a includes a first electrode 11, a second electrode 12, and a dielectric 20. The dielectric 20 is disposed between the first electrode 11 and the second electrode 12. The dielectric 20 includes a predetermined complex oxide. The complex oxide includes Cs, at least one selected from the group consisting of Ti, Zr, and Hf, and W. When the dielectric 20 includes such a complex oxide, the relative dielectric constant of the dielectric 20 is likely to be high, and the capacitor 1a is likely to have a high electrostatic capacitance. In addition, the dielectric breakdown field of the dielectric 20 is likely to be high. Therefore, the energy density of the capacitor 1a is likely to be increased. The complex oxide may include a trace amount of impurities. The trace amount of impurities may be composed of elemental species other than the above-mentioned elemental species. For example, the trace amount of impurities may be 5 mass% or less with respect to 100 mass parts of the complex oxide.

[0019] The composition of the composite oxide is not limited to a specific composition as long as it is composed of Cs, at least one selected from the group consisting of Ti, Zr, and Hf, and W. The composite oxide may be, for example, Cs α X β W γ O δ In this composition, X is at least one selected from the group consisting of Ti, Zr, and Hf. This composition satisfies the conditions of 0.9≦α≦1.1, 0.25≦β≦1, 1≦γ≦2, and 5.5≦δ≦6.5. When the composite oxide has such a composition, the relative dielectric constant of the dielectric 20 tends to be higher, and the dielectric breakdown electric field of the dielectric 20 tends to be higher.

[0020] The composition may satisfy the condition α=1. The composition may satisfy the condition 0.3≦β≦0.9, 0.3≦β≦0.8, 0.3≦β≦0.7, 0.3≦β≦0.6, 0.4≦β≦0.6, or β=0.5. The composition may satisfy the condition γ=1.5. The composition may satisfy the condition δ=6.

[0021] The crystal structure of the complex oxide is not limited to a specific crystal structure. The complex oxide has, for example, a pyrochlore type crystal structure. This makes it easier for the dielectric constant of the dielectric 20 to be higher, and the dielectric breakdown field of the dielectric 20 to be higher.

[0022] The entire dielectric 20 may be composed of the composite oxide, or a part of the dielectric 20 may be composed of the composite oxide. In the dielectric 20, the composite oxide may form a continuous phase or a dispersed phase.

[0023] The dielectric constant of the dielectric 20 is not limited to a specific value. The dielectric constant of the dielectric 20 at room temperature may be higher than 50, may be 55 or more, may be 60 or more, may be 70 or more, may be 80 or more, or may be 100 or more at 1 MHz. The room temperature is, for example, a specific temperature in the range of 20°C to 25°C. The dielectric constant of the dielectric 20 at room temperature is, for example, 10000 or less at 1 MHz. In other words, the dielectric constant of the dielectric 20 at room temperature is, for example, 55 or more and 10000 or less at 1 MHz.

[0024] The dielectric breakdown field of the dielectric 20 is not limited to a specific value. The dielectric breakdown field of the dielectric 20 at -273°C is, for example, 0.1 V / nm or more, may be 5 V / nm or more, or may be 10 V / nm or more. The dielectric breakdown field of the dielectric 20 at -273°C is, for example, 50 V / nm or less. In other words, the dielectric breakdown field of the dielectric 20 at -273°C may be 10 V / nm or more and 30 V / nm or less.

[0025] As shown in FIG. 1, the dielectric 20 in the capacitor 1a is, for example, a film. The method of disposing the dielectric 20 in the capacitor 1a is not limited to a specific method. The dielectric 20 may be formed by, for example, spin coating, inkjet, die coating, roll coating, bar coating, Langmuir-Blodgett, dip coating, or spray coating. This makes it easier for the dielectric 20 to have a high relative dielectric constant and for the dielectric breakdown field of the dielectric 20 to be higher. The dielectric 20 may be formed by sputtering, anodization, vacuum evaporation, pulsed laser deposition (PLD), atomic layer deposition (ALD), or chemical vapor deposition (CVD).

[0026] 1, the dielectric 20 is disposed, for example, between the first electrode 11 and the second electrode 12 in the thickness direction of the dielectric 20. The second electrode 12 covers, for example, at least a portion of the dielectric 20.

[0027] The materials forming the first electrode 11 and the second electrode 12 are not limited to a specific material. Each of the first electrode 11 and the second electrode 12 includes, for example, a metal. The first electrode 11 includes, for example, a valve metal. Examples of the valve metal are Al, Ta, Nb, and Bi. The first electrode 11 includes, for example, at least one valve metal selected from the group consisting of Al, Ta, Nb, and Bi. The first electrode 11 may include a precious metal such as gold or platinum, may include Ni, or may include a metal element of group 13, group 14, or group 15.

[0028] The second electrode 12 may contain, for example, a valve metal such as Al, Ta, Nb, or Bi, a precious metal such as gold, silver, or platinum, Ni, or a metal element of Group 13, Group 14, or Group 15. The second electrode 12 contains, for example, at least one selected from the group consisting of Al, Ta, Nb, Bi, gold, silver, platinum, and Ni.

[0029] 1, the first electrode 11 has a principal surface 11p. One principal surface of the dielectric 20 is in contact with the principal surface 11p, for example. The second electrode 12 has a principal surface 12p parallel to the principal surface 11p, for example. The other principal surface of the dielectric 20 is in contact with the principal surface 12p, for example.

[0030] Fig. 2 is a cross-sectional view showing another example of a capacitor of the present disclosure. Capacitor 1b shown in Fig. 2 is configured similarly to capacitor 1a, except for parts that will be particularly described. Components of capacitor 1b that are the same as or correspond to those of capacitor 1a are given the same reference numerals, and detailed description will be omitted. The description of capacitor 1a also applies to capacitor 1b as long as there is no technical contradiction. The same also applies to capacitors 1c and 1d described below.

[0031] As shown in Fig. 2, the capacitor 1b is an electrolytic capacitor. In the capacitor 1b, at least a part of the first electrode 11 is porous. With such a configuration, the surface area of ​​the first electrode 11 is likely to be large, and the capacitor 1b is likely to have a high capacitance. Such a porous structure can be formed by, for example, a method such as etching a metal foil or sintering a powder.

[0032] 2, for example, a film of a dielectric 20 is disposed on the surface of the porous portion of the first electrode 11. The method of forming the dielectric 20 can be, for example, spin coating, inkjet, die coating, roll coating, bar coating, Langmuir-Blodgett, dip coating, or spray coating. The dielectric 20 may be formed by, for example, sputtering, anodization, vacuum deposition, PLD, ALD, or CVD.

[0033] The first electrode 11 includes a valve metal such as Al, Ta, Nb, Zr, Hf, and Bi. The second electrode 12 may include, for example, a solidified silver-containing paste, a carbon material such as graphite, or both a solidified silver-containing paste and a carbon material such as graphite.

[0034] In capacitor 1b, electrolyte 13 is disposed between first electrode 11 and second electrode 12. In detail, electrolyte 13 is disposed between dielectric 20 and second electrode 12. In capacitor 1b, for example, second electrode 12 and electrolyte 13 form cathode 15. In capacitor 1b, electrolyte 13 is disposed so as to fill voids around a porous portion of first electrode 11, for example.

[0035] The electrolyte 13 includes, for example, at least one selected from the group consisting of an electrolytic solution and a conductive polymer. Examples of the conductive polymer include polypyrrole, polythiophene, polyaniline, and derivatives thereof. The electrolyte 13 may be a manganese compound such as manganese oxide. The electrolyte 13 may include a solid electrolyte.

[0036] The electrolyte 13 containing a conductive polymer can be formed by performing chemical polymerization, electrolytic polymerization, or both chemical polymerization and electrolytic polymerization of a raw material monomer on the dielectric 20. The electrolyte 13 containing a conductive polymer may also be formed by depositing a solution or dispersion of the conductive polymer on the dielectric 20.

[0037] Fig. 3 is a cross-sectional view showing yet another example of a capacitor according to the present disclosure. In the capacitor 1c shown in Fig. 3, at least a part of the first electrode 11 is porous. With such a configuration, the surface area of ​​the first electrode 11 is likely to be large, and the capacitor 1c is likely to have a high capacitance. Such a porous structure can be formed by, for example, a method such as etching a metal foil and sintering a powder.

[0038] 3, for example, a film of the dielectric 20 is disposed on the upper part of the porous part of the first electrode 11. For example, spin coating, inkjet, die coating, roll coating, bar coating, Langmuir-Blodgett, dip coating, or spray coating can be used as a method for forming the dielectric 20. In the capacitor 1c, the dielectric 20 is disposed so as to fill the voids around the porous part of the first electrode 11, for example.

[0039] FIG. 4 is a cross-sectional view showing yet another example of the capacitor of the present disclosure. In the capacitor 1d shown in FIG. 4, the dielectric 20 is, for example, a film. In this film, a different dielectric 22 different from the dielectric 20 is dispersed and arranged. As a method for forming this film, spin coating, inkjet, die coating, roll coating, bar coating, Langmuir-Blodgett, dip coating, or spray coating can be adopted. For example, a film containing the dielectric 20 and the different dielectric 22 is obtained by forming a coating of a precursor liquid containing the raw material of the dielectric 20 and particles of the different dielectric 22 by the above-mentioned method. This film may be formed by sputtering, anodization, vacuum deposition, PLD, ALD, or CVD.

[0040] The heterogeneous dielectric 22 is not limited to a specific dielectric as long as it is a dielectric of a different type from the dielectric 20. The heterogeneous dielectric 22 has, for example, a higher dielectric constant than that of the dielectric 20. The heterogeneous dielectric 22 may be, for example, a perovskite compound such as BaTiO3, PbTiO3, and SrTiO3, or may be a layered perovskite compound. The heterogeneous dielectric 22 may include at least one selected from the group consisting of a Ruddlesden-Popper compound, a Dion-Jacobson compound, a tungsten bronze compound, and a pyrochlore compound.

[0041] The size of the particles of the different dielectric material 22 is not limited to a specific value. The particles of the different dielectric material 22 have a size of, for example, 1 nm or more and 100 nm or less.

[0042] FIG. 5 is a diagram showing a schematic example of an electric circuit according to the present disclosure. The electric circuit 3 includes a capacitor 1a. The electric circuit 3 may be an active circuit or a passive circuit. The electric circuit 3 may be a discharge circuit, a smoothing circuit, a decoupling circuit, or a coupling circuit. Since the electric circuit 3 includes the capacitor 1a, the electric circuit 3 is likely to exhibit a desired performance. For example, the noise in the electric circuit 3 is likely to be reduced by the capacitor 1a. The electric circuit 3 may include a capacitor 1b, 1c, or 1d instead of the capacitor 1a.

[0043] Fig. 6 is a diagram illustrating an example of a circuit board according to the present disclosure. As illustrated in Fig. 6, the circuit board 5 includes a capacitor 1a. For example, an electric circuit 3 including the capacitor 1a is formed on the circuit board 5. The circuit board 5 may be an embedded board or a motherboard. The circuit board 5 may include a capacitor 1b, 1c, or 1d instead of the capacitor 1a.

[0044] FIG. 7 is a diagram showing a schematic diagram of an example of the device of the present disclosure. As shown in FIG. 7, the device 7 includes, for example, a capacitor 1a. The device 7 includes, for example, a circuit board 5 including the capacitor 1a. Since the device 7 includes the capacitor 1a, the device 7 is likely to exhibit a desired performance. The device 7 may be an electronic device, a communication device, a signal processing device, or a power supply device. The device 7 may be a server, an AC adapter, an accelerator, or a flat panel display such as a liquid crystal display (LCD). The device 7 may be a USB charger, a solid state drive (SSD), an information terminal such as a PC, a smartphone, or a tablet PC, or an Ethernet switch.

[0045] (Additional Note) From the above description, the following techniques are disclosed.

[0046] (Technology 1) A first electrode; A second electrode; a dielectric material including a complex oxide and disposed between the first electrode and the second electrode; The composite oxide is Cs and At least one selected from the group consisting of Ti, Zr, and Hf; W, which is composed of Capacitor.

[0047] (Technology 2) The composite oxide is Cs α X β W γ O δ The composition is represented by In the above composition, X is at least one selected from the group consisting of Ti, Zr, and Hf; The composition satisfies the conditions of 0.9≦α≦1.1, 0.25≦β≦1, 1≦γ≦2, and 5.5≦δ≦6.5. The capacitor according to technique 1.

[0048] (Technology 3) The composite oxide has a pyrochlore type crystal structure. The capacitor according to any one of claims 1 to 2.

[0049] (Technology 4) Cs and At least one selected from the group consisting of Ti, Zr, and Hf; and a composite oxide containing W, Dielectric for capacitors.

[0050] (Technology 5) An electric circuit comprising the capacitor according to any one of claims 1 to 3.

[0051] (Technology 6) A circuit board comprising the capacitor according to any one of claims 1 to 3.

[0052] (Technology 7) A device comprising the capacitor according to any one of claims 1 to 3. EXAMPLES

[0053] The present disclosure will be described in detail below with reference to examples. Note that the following examples are merely illustrative and the present disclosure is not limited to the following examples.

[0054] (Evaluation of relative dielectric constant) Fig. 8 is a diagram showing a schematic diagram of a method for evaluating the relative dielectric constant of the dielectrics according to each example. As shown in Fig. 8, the pressure molding die 30 had an upper punch 31, a frame 32, and a lower punch 33. The upper punch 31 and the lower punch 33 were each made of stainless steel having electronic conductivity. The frame 32 was made of polycarbonate having electrical insulation.

[0055] Using the pressure molding die 30, the dielectric constant of the dielectric of each example was measured by the following method. In a dry atmosphere having a dew point of -30°C or less, the powdery dielectric of each example was filled inside the pressure molding die 30 to obtain a sample Sa. Inside the pressure molding die 30, a pressure P of 300 MPa was applied to the sample Sa using the upper punch 31 and the lower punch 33. While the pressure P was applied to the sample Sa, the upper punch 31 and the lower punch 33 were connected to a potentiostat 50 equipped with a frequency response analyzer. As the potentiostat 50, VersaSTAT4 manufactured by Princeton Applied Research was used. The upper punch 31 was connected to the working electrode and the potential measuring terminal of the potentiostat 50. The lower punch 33 was connected to the counter electrode and the reference electrode of the potentiostat 50. The impedance of the sample Sa was measured by an electrochemical impedance measurement method at room temperature (22°C). In this manner, the dielectric constant ε' at 1 MHz of the sample according to each example was measured. r The relative dielectric constant ε' was measured. r The capacitance of each sample was measured, and the relative dielectric constant ε' was determined based on the measured capacitance, the thickness of the sample Sa, and the electrode area.r is corrected by the pellet filling rate f using equation (1), and the relative dielectric constant ε r In formula (1), ε Air is the relative dielectric constant of the air, and the relative dielectric constant ε r The filling rate f was calculated using equation (2). pellet is the density of the sample Sa, and ρ is the density calculated from the crystal structure of the dielectric. The results are shown in Table 1.

[0056] logε r =(logε' r -(1-f)logε Air ) / f formula (1) f=ρ pellet / ρ Equation (2) (Evaluation of dielectric breakdown field) Band gap E obtained from first-principles calculations g The dielectric breakdown field E of the dielectrics according to each of the examples and comparative examples was calculated based on the following formulas (3a) and (3b) with reference to Wang, Li-Mo. "Relationship between Intrinsic Breakdown Field and Bandgap of Materials." 2006 25th International Conference on Microelectronics. IEEE, 2006. In the following formulas, E and E g The units are V / nm and eV, respectively. The calculation results are shown in Table 1.

[0057] E = 1.36 × (E g / 4) 3 (E g <4) Equation (3a) E = 1.36 × (E g / 4) (E g ≧4) Equation (3b) (Energy density evaluation) The relative dielectric constant ε of the dielectric obtained from the measurement results rBased on the dielectric breakdown field E [V / nm] calculated as above, the energy density W of the dielectric material according to each example was calculated from the following formula (4). In formula (4), ε0 is the dielectric constant of a vacuum, and the unit of the energy density W is [Wh / liter (L)].

[0058] W = (1 / 7.2) x 10 12 ε0 ε r (E) 2 Formula (4) (Crystal structure analysis) In order to identify the crystal structure of the dielectric according to Example 1, an X-ray diffraction (XRD) measurement was carried out. In this measurement, Cu-Kα radiation was used as the X-ray, and the measurement was carried out in a dry argon atmosphere. FIG. 9 is a graph showing the XRD pattern of the dielectric according to each Example. In this graph, the horizontal axis indicates the diffraction angle 2θ, and the vertical axis indicates the intensity of X-ray diffraction. FIG. 9 shows the XRD pattern of Cs2HfW3O obtained from the Inorganic Crystal Structure Database (ICSD). 12 , Cs2ZrW3O 12 , and Cs2TiW3O 12 4 shows reference data for the X-ray diffraction pattern of

[0059] <Example 1> 3 g of raw material powder containing Cs2CO3, TiO2, and WO3 was prepared so that the condition of Cs2CO3 mass amount: TiO2 mass amount: WO3 mass amount = 1:1:3 was satisfied. This raw material powder was pulverized and mixed in a mortar. The mixed powder thus obtained was placed in a pressure molding die and pressed at a pressure of 20 MPa to produce a pellet. The obtained pellet was fired in air at 850°C for 80 hours. The fired pellet was pulverized again in a mortar to obtain a powdered dielectric according to Example 1. The dielectric according to Example 1 was CsTi 0.5 W 1.5 It had a composition represented as O6.

[0060] <Example 2> 3 g of raw material powder containing Cs2CO3, ZrO2, and WO3 was prepared so that the condition of Cs2CO3 mass amount: ZrO2 mass amount: WO3 mass amount = 1:1:3 was satisfied. This raw material powder was pulverized and mixed in a mortar. The mixed powder thus obtained was placed in a pressure molding die and pressed at a pressure of 20 MPa to form a pellet. The obtained pellet was fired in air at 850°C for 80 hours. The fired pellet was pulverized again in a mortar. The obtained powder was placed in a pressure molding die again and pressed at a pressure of 20 MPa to form a pellet. The obtained pellet was fired in air at 900°C for 15 hours. The fired pellet was pulverized again in a mortar. A powdered dielectric according to Example 2 was obtained. The dielectric according to Example 2 was CsZr 0.5 W 1.5 It had a composition represented as O6.

[0061] <Example 3> 3 g of raw material powder containing Cs2CO3, HfO2, and WO3 was prepared so that the condition of Cs2CO3 mass: HfO2 mass: WO3 mass = 1:1:3 was satisfied. This raw material powder was pulverized and mixed in a mortar. The mixed powder thus obtained was placed in a pressure molding die and pressed at a pressure of 20 MPa to produce a pellet. The obtained pellet was fired in air at 850°C for 80 hours. The fired pellet was pulverized again in a mortar. The obtained powder was placed in a pressure molding die again and pressed at a pressure of 20 MPa to produce a pellet. The obtained pellet was fired in air at 900°C for 15 hours. The fired pellet was pulverized again in a mortar. In this way, a powdered dielectric according to Example 3 was obtained. The dielectric according to Example 3 was CsHf 0.5 W 1.5 It had a composition represented as O6.

[0062] <Comparative Example 1> Relative dielectric constant ε of Nd2Hf2O7 listed in ICSD r and band gap E g The dielectric breakdown field E and energy density W of Nd2Hf2O7 were calculated based on the formulas (3a) and (3b) and (4). The results are shown in Table 1.

[0063] <Comparative Example 2> The relative dielectric constant ε of BaTa2O6 listed in ICSD r and band gap E g The dielectric breakdown field E and energy density W of BaTa2O6 were calculated based on the formulas (3a) and (3b) and (4). The results are shown in Table 1.

[0064] <Comparative Example 3> The dielectric constant ε of BaNb2O6 listed in ICSD r and band gap E g The dielectric breakdown field E and energy density W of BaNb2O6 were calculated based on the formulas (3a) and (3b) and the formula (4). The results are shown in Table 1.

[0065] As shown in Table 1, the dielectrics according to each Example had a higher relative dielectric constant than the composite oxides in the Comparative Examples. In addition, it was suggested that the dielectrics according to each Example had a high dielectric breakdown field E. Therefore, it was suggested that a dielectric containing a composite oxide containing Cs, at least one selected from the group consisting of Ti, Zr, and Hf, and W is advantageous in terms of increasing the capacitance and dielectric breakdown field of a capacitor.

[0066] According to FIG. 9, the XRD patterns of the dielectrics according to Examples 1, 2, and 3 were obtained from ICSD. 12 , Cs2ZrW3O 12 , and Cs2HfW3O 12 This was consistent with the reference data for the X-ray diffraction pattern of 1. This suggests that the composite oxide contained in the dielectric material according to each example has a pyrochlore type crystal structure.

[0067] [Table 1] [Industrial Applicability]

[0068] The capacitors of the present disclosure are useful in terms of capacitance and dielectric breakdown field. [Explanation of symbols]

[0069] 1a, 1b, 1c, 1d capacitors 3 Electrical Circuits 5 Circuit Board 7 Equipment 11 First electrode 12 Second electrode 20 Dielectrics

Claims

1. A first electrode; A second electrode; a dielectric material including a complex oxide and disposed between the first electrode and the second electrode; The composite oxide is Cs and At least one selected from the group consisting of Ti, Zr, and Hf; W, Capacitor.

2. The composite oxide is Cs α X β W γ O δ The composition is represented by In the above composition, X is at least one selected from the group consisting of Ti, Zr, and Hf; The composition satisfies the conditions of 0.9≦α≦1.1, 0.25≦β≦1, 1≦γ≦2, and 5.5≦δ≦6.

5. The capacitor of claim 1 .

3. The composite oxide has a pyrochlore type crystal structure. The capacitor of claim 1 .

4. Cs and At least one selected from the group consisting of Ti, Zr, and Hf; and a composite oxide containing W; Dielectric for capacitors.

5. An electric circuit comprising the capacitor according to any one of claims 1 to 3.

6. A circuit board comprising the capacitor according to claim 1 .

7. An apparatus comprising the capacitor according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Dielectric film

    JP2000188016A

  • Metal oxide thin films for high dielectric constant applications

    JP2003502837A

  • Laminate and method for producing the same

    JP2013121914A

  • Heat ray-shielding dispersion material, coating liquid for forming heat ray-shielding dispersion material, and heat ray-shielding body

    JP2015044921A

  • Electromagnetic wave-absorbing particle dispersion and electromagnetic wave-absorbing transparent laminated substrate

    WO2019031242A1